2000
DOI: 10.1002/1521-3773(20001016)39:20<3667::aid-anie3667>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Living Coordination Polymerization of Allene Derivatives Bearing Hydroxy Groups by π-Allylnickel Catalyst

Abstract: Well‐defined poly(alcohol)s were prepared directly by the living coordination polymerization of allene derivatives bearing hydroxy groups with [{(π‐allyl)NiOCOCF3}2]/PPh3 as an initiator (see scheme). R=CH2OH, CHCH3OH, C(CH3)2OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…The molecular weights of PMHDO increased linearly with increasing feed ratios, and the molecular weight distributions of PMHDO remained narrow throughout the polymerization ( M w / M n < 1.23). These results affirmed the living nature of this polymerization system 10…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The molecular weights of PMHDO increased linearly with increasing feed ratios, and the molecular weight distributions of PMHDO remained narrow throughout the polymerization ( M w / M n < 1.23). These results affirmed the living nature of this polymerization system 10…”
Section: Resultssupporting
confidence: 78%
“…The living coordination polymerization of allene derivatives initiated by [(η 3 ‐allyl)NiOCOCF 3 ] 2 ( 2 ) can proceed under mild conditions to give well‐defined polymers in high yields; their molecular weights can be controlled by the feed ratio, and their molecular weight distributions are always narrow 3–9. Also, the stable, living π‐allyl nickel end enables the block copolymerization of allene derivatives, and the molecular weight and composition of the block copolymer can be adjusted by the feed ratio 10–12. However, the polymerizations of common vinyl monomers such as styrene and acrylate cannot be initiated by 2 , and well‐defined copolymers of allene derivatives with common vinyl monomers cannot be obtained by this kind of living coordination polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the molecular weights of PMHDO homopolymers increased linearly with the increase of the feed ratio and the molecular weight distributions remained narrow throughout the polymerization (M w /M n < 1.23). These results verified the living nature of the present polymerization system [7]. …”
Section: Graft Copolymerization Of Methyl Methacrylatementioning
confidence: 99%
“…By this way, molecular weight of the polymer can be controlled by the feed ratio of the monomer to the initiator and molecular weight distribution of the polymer can be kept narrow. Also, the block copolymerization of allene derivatives were carried out due to the stability of the living pallylnickel end group and the molecular weights can be tuned by the feed ratio [7]. Since [(h 3 -allyl)NiOCOCF 3 ] 2 can not initiate the polymerization of vinyl monomers such as styrene, acrylate and methacrylate, etc.…”
Section: Introductionmentioning
confidence: 99%